SUS IN FOCUS: THE USE OF A DIGITAL RPG TO SUPPORT HEALTH EDUCATION (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2026)
This study explores health education through alternative methodologies, employing didactic tools, specifically role-playing games (RPG´S), with an emphasis on the structure and operation of Unified Health System (SUS). The study had two main objectives: first, to develop a demonstrative version (demo) of the game, aiming to illustrate its gameplay and applicability for teaching and learning; second, to understand how an electronic RPG focused on the SUS could support health education. This is an experimental study that combines qualitative and quantitative methods. A semi-structured questionnaire was designed for online interviews with students over 18 years old, enrolled in undergraduate health related programs. Data analysis was conducted using Bardin’s content analysis method, which led to the identification of three thematic categories: innovation in education, benefits of digital education and drawbacks of digital education, A total of 36 students were interviewed, and their responses indicated that educational games can serve as an innovative alternative methodology, particularly in the field of health, by promoting student immersion and active participation. Among the identified benefits were ease of access and increased interest in the content. Conversely, the negative aspects included excessive screen time, limited internet access, risk of distraction, and the perception that playful learning might not be taken seriously. It is concluded that, despite the challenges, gamification serves as a positive incentive for health learning, making the process more accessible, dynamic and engaging.
Keywords: Health Education; Unified Health System; Education Games; Gamification